The coronavirus conundrum – New Omicron variant - New concerns - The Woman - Pacheco-Romero, José (2021)
A new SARS-CoV-2 virus variant of consideration appeared, whose aggressiveness seems to be higher due to its mutations and we do not know how it will affect the population, women, vaccines.